Revitalisasi Kesenian Islam Jawa melalui Transformasi Artistik Gembrung dalam Aransemen Orkestra Lagu Khotaman Nabi - Dadang Wahyu Saputra (CV Omah Kreator, 2026)
The rapid development of contemporary performing arts has encouraged traditional arts to adapt in order to remain relevant without losing their cultural identity. One such effort is reflected in the orchestral arrangement of Khotaman Nabi, a repertoire of the Javanese Islamic performing art Gembrung, which integrates traditional musical elements with Western orchestral practices. This study aims to analyze the artistic transformation of Gembrung into an orchestral performance and to explain how this transformation functions as a strategy for revitalizing Javanese Islamic performing arts. The study employed a practice-led artistic research approach, using the orchestral score of Khotaman Nabi as the primary data source, supported by documentation of the creative process and relevant literature. Data were analyzed through musical analysis, interpretative analysis, and contextual interpretation within the perspectives of orchestration, cultural hybridity, and cultural revitalization. The findings indicate that the orchestral arrangement preserves the essential musical identity of Gembrung through the continuity of its vocal melody, the central role of the dhalang, and the preservation of Islamic lyrical content, while simultaneously enriching its musical expression through harmonic development, string orchestration, textural expansion, and choral integration. Rather than replacing the traditional form, orchestration serves as an artistic medium that broadens the performance context of Gembrung and strengthens its cultural relevance for contemporary audiences. This study concludes that orchestration can be understood as an artistic strategy for revitalizing Javanese Islamic performing arts by creating a dialogical relationship between local traditions and modern musical practices without diminishing the religious and cultural values embedded in the tradition.